A research framework and a mechanistic host-interaction model for insects that use multiple host species: theoretical considerations and practical consequences - Rafter, Michelle Amy; Walter, Gimme H. (Frontiers in Ecology and Evolution, 2025)
Practical outcomes that are sought for various pest management systems involving insects are likely to be strengthened if the relevant underlying theoretical models and premises (which are often tacit) are taken into serious consideration. To illustrate this point, we revisit the research framework developed to help unravel the ecology of insects that use multiple host species, with a focus on herbivorous species (although the principles hold also for parasitoids and even predatory insects). The framework comprises four research questions that focus on the pattern of host species use (as quantified in the field) and the underlying mechanistic processes that result in the insects that use multiple host species being labelled as ‘generalist’. Results that derive from these research questions have led to the development of a general model to explain how female insects (of any species) behave with respect to the different host species with which they interact, and in relation to the condition of the plants and the recent history of the ovipositing females. This background allows us to then explore the theoretical and practical consequences of the research framework and the mechanistic host-interaction model. We do so with reference to a particular area of applied entomology, that of classical weed biocontrol. Also considered are the historical outcomes from the practice of an applied entomological discipline that relies on the stability and accurate delimitation of the host recognition mechanism of biocontrol agents.